Potential impact of systematic and random errors in blood pressure measurement on the prevalence of high office blood pressure in the United States. Issue 3 (9th February 2022) - Sakhuja, Swati; Jaeger, Byron C.; Akinyelure, Oluwasegun P.; Bress, Adam P.; Shimbo, Daichi; Schwartz, Joseph E.; Hardy, Shakia T.; Howard, George; Drawz, Paul; Muntner, Paul
Abstract: The authors examined the proportion of US adults that would have their high blood pressure (BP) status changed if systolic BP (SBP) and diastolic BP (DBP) were measured with systematic bias and/or random error versus following a standardized protocol. Data from the 2017–2018 National Health and Nutrition Examination Survey (NHANES; n = 5176) were analyzed. BP was measured up to three times using a mercury sphygmomanometer by a trained physician following a standardized protocol and averaged. High BP was defined as SBP ≥130 mm Hg or DBP ≥80 mm Hg. Among US adults not taking antihypertensive medication, 32.0% (95%CI: 29.6%, 34.4%) had high BP. If SBP and DBP were measured with systematic bias, 5 mm Hg for SBP and 3.5 mm Hg for DBP higher and lower than in NHANES, the proportion with high BP was estimated to be 44.4% (95%CI: 42.6%, 46.2%) and 21.9% (95%CI 19.5%, 24.4%). Among US adults taking antihypertensive medication, 60.6% (95%CI: 57.2%, 63.9%) had high BP. If SBP and DBP were measured 5 and 3.5 mm Hg higher and lower than in NHANES, the proportion with high BP was estimated to be 71.8% (95%CI: 68.3%, 75.0%) and 48.4% (95%CI: 44.6%, 52.2%), respectively. If BP was measured with random error, with standard deviations of 15 mm Hg for SBP and 7 mm Hg for DBP, 21.4% (95%CI: 19.8%, 23.0%) of US adults not taking antihypertensive medication and 20.5% (95%CI: 17.7%, 23.3%) taking antihypertensive medication had their high BP status re‐categorized. In conclusions, measuring BP with systematic or random errors may result in the misclassification of high BP for a substantial proportion of US adults.